Предмет: Алгебра, автор: цЫрка4

log0,2(x-2)+log0,2(x)>log0,2(2x-3). Нужно решение)

Ответы

Автор ответа: kirichekov
14
log₀,₂(x-2)+log₀,₂x>log₀,₂(2x-6)
ОДЗ:
{x-2>0       {x>2         {x>2
x>0             x>0         x>0     =>   x>1,5
2x-3>0       2x>3       x>1,5

log₀,₂((x-2)*x)>log₀,₂(2x-3)
log₀,₂(x²-2x)>log₀,₂(2x-3)
0<0,2<0
 знак неравенства меняем
x²-2x<2x-3
x²-4x+3<0  метод интервалов
1. х²-4х+3=0
x₁=3, x₁=1
     +             -               +
-----------|--------------|----------- x
             1                3
x∈(1;3)
x>1,5   =>
x∈(1,5 ; 3)

Похожие вопросы